An Inventory of Ants (Hymenoptera: Formicidae) at Melawi Sandy Beach, Bachok, Kelantan. - Abdullah, Nurul Ashikin; Hashim, Rosli (Malaysian Journal of Science, 2010)
An inventory of ant (Hymenoptera: Formicidae) fauna diversity was carried out at Melawi Beach, Bachok, Kelantan in April and May 2009. Two techniques, namely pitfall traps and manual hand collections were employed. A total of 28 species from 21 genera were recorded from an area in this coconut plantation. They belong to 6 subfamilies, comprising of Myrmicinae (9 species), Formicinae (13 species), Ponerinae (2 species), Dolichoderinae (2 species), Pseudomyrmecinae (1 species) and Aenictinae (1 species). The most common ants were the Weaver Ant (Oecophylla smaragdina) and the Yellow Crazy Ant (Anoplolepis gracilipes). They are tramps and are capable of invading and taking over local ants’ niches.